Characterization of Femur, Mandible and Bone Marrow-derived Mesenchymal Stromal Cells from Streptozotocin-Injected Mice - Vivatbutsiri, Philaiporn; Nowwarote, Nunthawan; Sawangmake, Chenphop; Chareonvit, Suconta; Pavasant, Prasit; Osathanon, Thanaphum (The Thai Journal of Veterinary Medicine, 2014)
Streptozotocin injection is simply shown to promote hyperglycemic condition in several species. In the present study, we aimed to characterize the femoral and mandibular bone features of streptozotocin-induced diabetic mice. In addition, the characteristics of bone marrow-derived mesenchymal stromal cells were evaluated. Results showed that streptozotocin injection resulted in significant weight loss and increase in fasting blood glucose levels in the animals. Compared to the control mice, significantly greater bone surface/bone volume value was noted in the mandible and the femur. On the contrary, trabecular thickness was significantly decreased in the metaphysis area of the femur. Further, the bone volume/total volume significantly decreased in the diaphysis area of the femur and in the mandible. Bone volume density was significantly decreased in the femur but not the mandible. Bone marrow-derived mesenchymal stromal cells (BMSC) isolated from the streptozotocin-induced diabetic mice exhibited marked reduction in colony forming unit ability and cell proliferation. However, the proliferation ability of BMSC was rescued with the presence of basic fibroblast growth factor (bFGF). Together, the results suggest that streptozotocin-induced diabetic condition affects bone phenotype and BMSC’s behaviors. In addition, bFGF supplementation could be used to expand BMSC in vitro. Thus, streptozotocin-injected mice could be utilized as a model to evaluate bone regeneration and engineering in diabetic condition.